2022
DOI: 10.5851/kosfa.2022.e26
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydrolysis Pre-Treatment by Flavourzyme on Meat Quality, Antioxidative Profiles, and Taste-Related Compounds in Samgyetang Breast Supplemented with Black Garlic

Abstract: This study aimed to carefully investigate the effect of hydrolysis using Flavourzyme on meat quality, antioxidative status, and taste-related compounds in breast of Samgyetang that was supplemented with black garlic (BG). Four different treatment groups were compared: (1) conventional Samgyetang (control), (2) Samgyetang hydrolyzed with Flavourzyme (1%, v/w) (FS), (3) Samgyetang made with the BG extract without hydrolysis (NBG), and (4) BG samgyetang pre-treated with Flavourzyme (1%, v/w) in a water bath at 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Moreover, Fernandez-Lopez et al [ 34 ], in a study on the effect of the addition of garlic extract to beef balls, came to similar conclusions. As reported by Barido et al [ 35 ], the addition of black garlic to meat products intensifies yellowing relative to the conventional product. This is confirmed by the results of Mancini et al [ 33 ] and Kim et al [ 7 ], where the addition of black garlic powder increased the value of the b* parameter.…”
Section: Resultsmentioning
confidence: 75%
“…Moreover, Fernandez-Lopez et al [ 34 ], in a study on the effect of the addition of garlic extract to beef balls, came to similar conclusions. As reported by Barido et al [ 35 ], the addition of black garlic to meat products intensifies yellowing relative to the conventional product. This is confirmed by the results of Mancini et al [ 33 ] and Kim et al [ 7 ], where the addition of black garlic powder increased the value of the b* parameter.…”
Section: Resultsmentioning
confidence: 75%
“…commonly used to promote an improved tenderness and flavour profiles [4,10,11]. With the above mentioned premises, this study aimed to investigate various extracts prepared from CM mushroom by reacting with other proteases (bromelain and flavorzyme) via enzymolysis on texture improvement of spent hen breast meat.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Its unique characteristics for having abundant content of macronutrients including polysaccharides and proteins, as well as micronutrients such as calcium, magnesium, phosphates, vitamins, and bioactive compounds are the reason for its broad functionalities for quality and health improvement [ 8 , 9 ]. Our previous study demonstrated the mushroom from family of Cordycipitaceae , particularly that of Cordyceps militaris (CM) mushroom exhibited superior properties for enhancing physicochemical attributes and texture profiles of meat-based products [ 8 , 10 , 11 ]. CM mushrooms are reported to contain diverse metabolites including adenine, adenosine, cordycepine, cordyheptapeptide, and polysaccharides that function as antifatigue, anti-inflammatory, immunomodulatory, and even anti-cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation